Treatment Strategies for Painful Pelvic Floor Conditions: A Focus on the Potential Benefits of Cannabidiol - Roberto Bonanni; Patrizia Ratano; Ida Cariati; Virginia Tancredi; Pierangelo Cifelli (Biomolecules)
Painful conditions of the pelvic floor include a set of disorders of the pelvic region, discreetly prevalent in the female population, in which pain emerges as the predominant symptom. Such disorders have a significant impact on quality of life as they impair couple relationships and promote states of anxiety and irascibility in affected individuals. Although numerous treatment approaches have been proposed for the management of such disorders, there is a need to identify strategies to promote muscle relaxation, counter pelvic pain, and reduce inflammation. The endocannabinoid system (ECS) represents a complex system spread throughout the body and is involved in the regulation of numerous physiological processes representing a potential therapeutic target for mood and anxiety disorders as well as pain management. Cannabidiol (CBD), acting on the ECS, can promote relief from hyperalgesia and allodynia typical of disorders affecting the pelvic floor and promote muscle relaxation by restoring balance to this delicate anatomical region. However, its use is currently limited due to a lack of evidence supporting its efficacy and harmlessness, and the mechanism of action on the ECS remains partially unexplored to this day. This comprehensive review of the literature examines the impact of pain disorders affecting the pelvic floor and major treatment approaches and brings together the main evidence supporting CBD in the management of such disorders.